Organisational learning as a Mediator of the Relationship between HR Outsourcing and Organisational Performance - Amer Ahmad, Al Anazi (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2017)
Link to publisher's homepage at http://ijbt.unimap.edu.my